ANALISIS POTENSIAL FINANCIAL DISTRESS PADA BANK UMUM KONVENSIONAL INDONESIA PERIODE 2018-2021 - Mintarti Ariani (Jurnal Ekonomi dan Bisnis, 2022)
The financial sector is one sector that is always overshadowed by various potential risks. These risks need to be anticipated by banks. Failure to manage risk will affect the bank's financial condition, one of which will lead to potential financial distress. Therefore, the ability of conventional commercial banks is needed to predict the potential for financial distress. The more banks cannot predict the potential for financial distress, it will lead to bankruptcy. This study aims to analyze the Zmijewski model (X-Score) in order to predict financial distress in conventional commercial banks. The object of research is the 13 conventional commercial banks that get the highest rating score from Forbes. Forbes released The World's Best Banks in 2022 by determining the best bank in Indonesia. The variable in this study is to take the cut-off value presented in the Zmijewski model (X-score). The study uses a descriptive approach with secondary data types sourced from the annual financial statements of the Financial Services Authority (OJK) from 2018-2021. The results show that in the Zmijewski model, based on the average X-score, there are 3 conventional commercial banks that are detected as having the potential to experience financial distress. The 3 conventional commercial banks are Bank Jago, Bank Neo Commerce and May Bank. The potential for financial distress is reflected in the results of the profitability ratio (return to assets), which during the observation period there was a tendency to decrease, especially at Bank Jago with the profitability ratio always losing